Self-reported visual symptoms and high visual demand activities in professional football players: a cross-sectional survey - Jorge, Jorge; Teixeira, José; Pinhão, Tiago; Delgado, Frederico; Salem, Alshaarawi; Martino, Francesco; Plainis, Sotiris (Frontiers in Sports and Active Living, 2023)
Background Vision is crucial for football players, impacting decision-making and athletic performance. Despite its global popularity, football lacks comprehensive evaluations of the impact of digital device use on ocular symptoms during high-demand activities. Purpose To gain knowledge about the time spent by football players in high visual demand activities, the symptoms associated with binocular vision dysfunction, and their relationship with sports performance. Methods A cross-sectional observational study was conducted in 2020 using an online survey targeting football players from Portugal, England, Spain, and Saudi Arabia. The survey, distributed over 5 weeks, aimed to collect data from approximately 5,000 football players. Information on player profiles, competitive levels, vision habits, and symptoms related to binocular vision dysfunctions was collected. The Convergence Insufficiency Symptom Survey (CISS) employed a 5-point Likert scale to indicate the average frequency of each symptom. Due to non-normality, non-parametric tests were used (p < 0.05). Specifically, Mann-Whitney U, Kruskal-Wallis, Chi-square, and Spearman's rank correlation tests were used as appropriate. Results Analyzing male professional football players (mean age: 27.4 ± 5.0 years, 95% CI, 26.7–28.1), it was found that 38.1% of the players had been called up to the national team and 6.9% had played over 50 games. Self-rated last season's performance had a mean score of 6.5 ± 2.1 (95% CI, 6.2–6.8)(on a scale of 1 to 10). Smartphone use exceeded 1 h daily for all players, with 36.0% surpassing 4 h. Visual symptoms, notably associated with smartphone use (35.5%), were observed. Regarding the CISS score, the mean was 7.1 ± 7.7 (IC95%: 6.6 to 8.8). A weak negative correlation (rho = −0.215, p = 0.003) emerged between CISS scores and self-perceived sports performance. Football players using prescription lenses had significantly higher CISS scores (11.9 ± 10.4, 95% CI, 12.3–7.7) compared to non-users (6.2 ± 6.8, 95% CI, 7.8–5.7) (p < 0.001). Conclusion This study reveals that professional football players engage in high visual demand tasks, notably on smartphones. One-third of the players link smartphone use to ocular symptoms. The Convergence Insufficiency Symptoms Survey indicates that 6.3% exhibit binocular vision dysfunction symptoms. Those with fewer ocular symptoms perceive that they have better sports performance than their counterparts.